Essential Oils and Extracts of Juniperus macrocarpa Sm. and Juniperus oxycedrus L.: Comparative Phytochemical Composition and Anti-Proliferative and Antioxidant Activities - Luciano Meringolo (Plants, 2022)
In this work, we conducted a comparative phytochemical, chemotaxonomic, and biological study of essential oils (EOs) and extracts (ethyl acetate and methanol) obtained from the leaves of Juniperusmacrocarpa and J. oxycedrus. The dominant compounds of J. macrocarpa EO, analysed by gas chromatography (GC) and gas chromatography-mass spectrometry (GC-MS), are α-pinene, sabinene, manoyl oxide, and germacrene D, whereas α-pinene, limonene, (Z,E)-farnesol, β-pinene, and γ-cadinene are the most representative volatiles of J. oxycedrus EOs. A multivariate analysis of EOs, included a selection of literature data comparing our samples to samples of J. oxycedrus/macrocarpa/deltoides from the Mediterranean area, was performed. As evident by high-performance liquid chromatography (HPLC) analyses, apigenin, (−)-epicatechin, and luteolin were abundant in J. oxycedrus extracts, while gallic acid, kaempferol-3-O-glucoside, and protocatechuic acid were the dominant constituents of J. macrocarpa extracts. EOs and extracts have been investigated for their potential antioxidant properties and anti-proliferative activity against lung adenocarcinoma (A549), breast cancer (MCF-7 and MDA-MB-231), and lung large cell carcinoma (COR-L23) human cell lines. The methanol and ethyl acetate extracts of J. oxycedrus exerted the most valuable antioxidant activity and exhibited the most promising activity against the COR-L23 cell line with an IC50 of 26.0 and 39.1 μg/mL, respectively, lower than that obtained with the positive control (IC50 of 45.5 μg/mL). To the best of our knowledge, this is the first report highlighting the anti-proliferative activity of J. oxycedrus and J. macrocarpa extracts against this lung cancer cell line. Our results indicate that J. oxycedrus may be considered a source of natural compounds with antioxidant and anti-proliferative effects that could be suitable for future applications.